The Reverse Side of a Legend: Otto Hahn in the Context of Nazi Germany - Grygar, Filip (Teorie vědy / Theory of Science, 2019)
The article aims to demystify a long-standing legend about Otto Hahn, who, as the Nobel Prize winner for chemistry for the discovery of the fission of heavy nuclei, is widely regarded as an academic figurehead in the world of science. He was considered a symbol of so-called German decency and responsibility; he was a model example of an anti-Nazi scientist who did not collaborate with the criminality of the regime in its warmongery. It was only from the 1990s onwards that historians gained access to new archival materials, which allowed for a comprehensive picture of Hahn’s work in Nazi Germany and his involvement in uranium research during wartime, whose aim was construction of nuclear reactors and bombs.